If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1w + 13 = 5w + -5 Reorder the terms: 13 + -1w = 5w + -5 Reorder the terms: 13 + -1w = -5 + 5w Solving 13 + -1w = -5 + 5w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-5w' to each side of the equation. 13 + -1w + -5w = -5 + 5w + -5w Combine like terms: -1w + -5w = -6w 13 + -6w = -5 + 5w + -5w Combine like terms: 5w + -5w = 0 13 + -6w = -5 + 0 13 + -6w = -5 Add '-13' to each side of the equation. 13 + -13 + -6w = -5 + -13 Combine like terms: 13 + -13 = 0 0 + -6w = -5 + -13 -6w = -5 + -13 Combine like terms: -5 + -13 = -18 -6w = -18 Divide each side by '-6'. w = 3 Simplifying w = 3
| 2w+56=176 | | 1.25x+5=-3 | | 24x=27x-6 | | -3.7y-5.7=-0.8y+3 | | 3(x+1)-2x=x+3 | | 2y+40=100 | | -4x+-9=-5-6x | | 10x+4=4x+7 | | 3(2m-4)=2m+4m-4 | | .75a+.75a+a=15 | | 9v-8(1+6v)= | | 24+2y+13=20+4y-19 | | 4(n+1)+3=-35-2n | | 3(2+r)-2r=2r+11 | | 8y-16=5y+2 | | 7(t-5)+8t=5(3t+5)-13 | | 13*k=52 | | 2x-5y+z=5 | | 5(k-2)-2(k+4)=6 | | 7+5x=-33 | | 10u-6=2(5u-3) | | y-19=-3y-12 | | 2x+52=90 | | w+3/5+4=6 | | 2y+5=-14 | | -6(p+8)=-6p+12 | | -4(y-1)+-3=25 | | 0.9=0.4x | | 3(5n+3)=5n-11 | | .35*90=l | | 4x-6(5-x)=14 | | v^2+2v+49=0 |